DOI: 10.14264/uql.2017.732
|View full text |Cite
|
Sign up to set email alerts
|

Becoming-(breastfeeding-)woman: women’s body practices and experiences at the intersection of breastfeeding, milk insufficiency, and milk sharing

Abstract: The breastfeeding body is a site of complex, contested, and conspicuously moralised practices that has long been a focus for research in the social sciences through to the arts and humanities. Often too the maternal, lactating body is situated within a biomedical frame that marks the milk-producing body as problematic, failing, and subject to and object of expert knowledges. In this frame, women who identify as producing "not enough milk" to feed their babies have been a significant focus.Despite this extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 144 publications
0
1
0
Order By: Relevance
“…This might culminate in the oversupply of breast milk and enable mothers to become potential milk donors 25 . Among the PMSh participants, significant factors related to milk sharing were, having >1 living child, giving birth to preterm babies, delivery through caesarean birth, and birth weight of child <2500 g. Many studies had reported that milk sharing was predominantly practiced by mothers of premature babies 21,26,27 and caesarean deliveries, 28 due to their lactation difficulties arising from mother–infant separation 29 . This often has led mothers to actively seek information about milk donation and gain better knowledge and practice in this regard 21,23 .…”
Section: Discussionmentioning
confidence: 99%
“…This might culminate in the oversupply of breast milk and enable mothers to become potential milk donors 25 . Among the PMSh participants, significant factors related to milk sharing were, having >1 living child, giving birth to preterm babies, delivery through caesarean birth, and birth weight of child <2500 g. Many studies had reported that milk sharing was predominantly practiced by mothers of premature babies 21,26,27 and caesarean deliveries, 28 due to their lactation difficulties arising from mother–infant separation 29 . This often has led mothers to actively seek information about milk donation and gain better knowledge and practice in this regard 21,23 .…”
Section: Discussionmentioning
confidence: 99%